Success behind advanced SWRO desalination plant. Issue 3 (May 2016) - Faigon, Miriam
Abstract : With ongoing water stress worldwide, finding long-term solutions to severe drought is imperative. This article looks at the commissioning and development of the Sorek Desalination Plant in Israel, the world's largest and most advanced SWRO desalination plant – and how a project of this size is tackled.